The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1108/02652320110399683
|View full text |Cite
|
Sign up to set email alerts
|

Customer adoption of tele‐banking technology:the case of Saudi Arabia

Abstract: Currently, the banking industry is facing increasingly demanding customers and quickly eroding competitive edges. Recent technological breakthroughs in various areas, however, offer opportunities for the banks to excel in customer service quality and convenience. One area of major breakthroughs is the service delivery systems that are reshaping the banking business radically. However, there are relatively few empirical analyses of the impact of tele‐banking service technology on customers. Examines the adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 17 publications
3
57
0
Order By: Relevance
“…Results chow that instruction is significant factor to explain internet banking adoption. This finding is consistent with the studies done by Karjaluoto et al, (2002), Mattila et al, 2003, Al-Ashban andBurney (2001), Stavins (2001) and Sathye, (1999). Moreover, results show that occupation appears to be significant influent users which are consistent with the finding of earlier studies, for example, Karjaluoto et al, 2002;Mattila et al, 2003 andSathye, 1999.…”
Section: Demographics Of the Samplesupporting
confidence: 83%
See 1 more Smart Citation
“…Results chow that instruction is significant factor to explain internet banking adoption. This finding is consistent with the studies done by Karjaluoto et al, (2002), Mattila et al, 2003, Al-Ashban andBurney (2001), Stavins (2001) and Sathye, (1999). Moreover, results show that occupation appears to be significant influent users which are consistent with the finding of earlier studies, for example, Karjaluoto et al, 2002;Mattila et al, 2003 andSathye, 1999.…”
Section: Demographics Of the Samplesupporting
confidence: 83%
“…Demographic factors have also been found to be associated with adoption of different banking channels, especially internet banking (Al-Ashban and Burney, 2001;Karjaluoto et al, 2002;Sathye, 1999). For instance, people with high educational attainment may have an aptitude for computers and possess good information processing skills.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…This proposition was confirmed by Meuter et al [25] who empirically approved income level as a key determinant of both customer readiness and customer experiment of different kinds of self-service technologies. Al-Ashban and Burney [1] also empirically approved income level as a considerable positive predictor of the customers' acceptance of Telebanking in Saudi Arabia. Likewise, according to Kolodinsky et al [20], the adoption rate of Internet banking channels was observed to be in the higher level among customers who have a higher income level instead of lower income customers.…”
Section: Incomementioning
confidence: 99%
“…Competition for customer deposits and investments is intense and banks strive to provide state-ofthe-art services for their customers, especially at the retail or personal level. Driven by the increasing penetration rate of mobile subscriptions in Saudi Arabia which reached 181 % in the third quarter of 2012 (Ethos Interactive, 2012) while 60% of the Saudi population own smart phones (CITC, 2012), Saudi banks have started to provide e-banking solutions for their clients through the usage of the land-line phones (Al-Ashban & Burney, 2001), internet (Al-Somali, Gholami & Clegg, 2009) and mobile phones (Al-Jabri & Sohail, 2012). Until recently, most customers have lined up in queues in banks' branches or at best use the Automatic Teller Machines (ATMs) to conduct their banking transactions.…”
Section: Introductionmentioning
confidence: 99%